(untitled) (American Journal of Management, 2024)
Based on the transactional theory of stress, people tend to adopt problem-oriented coping styles when they feel there are opportunities in the situation and can benefit from them. Positive effects of Artificial Intelligence (AI) on labor include increased income for certain management and skilled positions as well as the creation of new job opportunities. However, among its drawbacks are the jobs it replaces, which causes unemployment. According to resource conservation theory, concerns about job stability and persistence trigger the process of resource consumption, which wears people out emotionally (Xu, et.al., 2023). The study results provide the relationship among Artificial Intelligence (AI) opportunity perception, employees’ workplace well-being (WWB) and Informal Learning in the Workplace (ILW).